The investigation of toll-like receptor 3, 9 and 10 gene polymorphisms in Turkish rheumatoid arthritis patients - Etem, Ebru Onalan; Elyas, Halit; Ozgocmen, Salih; Yildirim, Arefe; Godekmerdan, Ahmet (Springer Heidelberg, 2011)
Toll-like receptors (TLRs) play an important role in the induction and regulation of the innate immune system or adaptive immune responses. Genetic variations within human TLRs have been reported to be associated with a range of immune-related diseases. This study was conducted to investigate the frequencies of TLR3 rs3775290, TLR9 rs187084, and TLR10 rs4129009 polymorphisms and to detect between polymorphisms and autoantibody positive as RF, collagen type II, anti-RNP, and anti-CCP in patient group. We performed a case-control study of 100 rheumatoid arthritis (RA) cases and 100 healthy controls matched on age, sex, and residence. All polymorphisms in TLRs were determined by polymerase chain reaction-based restriction fragment length polymorphism. Serum autoantibody level was measured using quantitative ELISA. SNPs were genotyped in all samples. Our results showed that TT genotype for SNP 1237 T/C increased the RA risk significantly (p < 0.05). No statistically significant differences were found in the TLR3 and TLR10 genotypes or allele distribution between RA patients and control individuals. No associations were noted with autoantibody production and TLR3, TLR9, and TLR10 polymorphisms genotypes (p > 0.05). Our study suggests that a single nucleotide polymorphism (rs187084) in TLR9 gene may be a susceptibility factor for RA in Turkish population. Further studies are required to explore the role of TLRs gene polymorphisms in the risk of RA, especially in ethnically different populations to confirm our results.
Keywords: TLRs; Polymorphism; Rheumatoid arthritis; PAMP